1994
DOI: 10.1111/j.1365-2478.1994.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Radar experiments in isotropic and anisotropic geological formations (granite and schists)1

Abstract: In order to understand various aspects of radar wave propagation, a survey of electromagnetic wave behaviour relative to the geological characteristics of the formations prospected was undertaken. The sites chosen for the tests were a granite quarry and an underground schist working. By investigating an electrically resistive isotropic site and a conductive anisotropic site, it was demonstrated that non-conventional use of a radar system (antennae raised, various orientations of the transmitter/receiver, etc.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 12 publications
(9 reference statements)
1
20
0
Order By: Relevance
“…Some of them are: Tillard (1994), Serzu et al (1996Serzu et al ( , 1998, Grasmueck (1996), Liner and Liner (1997), Dérobert and Abraham (2000), Pipan et al (2000), Seol et al (2001Seol et al ( , 2002, Lualdi and Zanzi (2003, 2004), and Orlando (2003. In Brazil, the following have reported the use of GPR on granites: , Botelho et al ( , 1999, Botelho and Mufti (1998), Souza and Porsani (2002), and Souza (2002).…”
Section: Introduction and Objectivesmentioning
confidence: 92%
“…Some of them are: Tillard (1994), Serzu et al (1996Serzu et al ( , 1998, Grasmueck (1996), Liner and Liner (1997), Dérobert and Abraham (2000), Pipan et al (2000), Seol et al (2001Seol et al ( , 2002, Lualdi and Zanzi (2003, 2004), and Orlando (2003. In Brazil, the following have reported the use of GPR on granites: , Botelho et al ( , 1999, Botelho and Mufti (1998), Souza and Porsani (2002), and Souza (2002).…”
Section: Introduction and Objectivesmentioning
confidence: 92%
“…For example, Nobes (1999) found that the response on temperate glaciers depends on the orientation of the antennas relative to the glacier flow direction; van Overmeeren (1994) noted that the response from sedimentary sequences varies depending on the orientation of the antennas relative to the dip of the beds; and Tillard (1994) observed that the response for radar experiments in granite and schist depends on the orientation of the antennas relative to the schistosity. Such observations are consistent with the character of the signal transmitted from a GPR antenna into the ground under different conditions (Annan et al, 1975 and Figure 1).…”
mentioning
confidence: 97%
“…Tillard [1994] has suggested that a schist with a much stronger preferred orientation than even the Fibbia gneiss may have electromagnetic wave velocities that vary by as much as 100% with orientation, with velocity along the schistosity direction being nearly twice that of the perpendicular direction. In the experiment described here, rms velocities also appear to vary with direction, though not as dramatically.…”
Section: Velocity Variation With Line Azimuthmentioning
confidence: 99%